Literature Review: An Overview of Moderate Lifestyle on the Incidence of Obesity - Attahmid, A. Ridhah Nurmy; Nasrudin, Hermiaty; Ramlian, Ramlian (Newinera Publisher, 2024)
This study aims to explore and analyze the relationship between a sedentary lifestyle and the incidence of obesity. The main focus of this research is to identify factors that contribute to the increasing prevalence of obesity in the context of a less active lifestyle, as well. The results of the study show a significant association between a sedentary lifestyle and an increased risk of prediabetes, underscoring the important role of community health centers in efforts to prevent metabolic diseases. The implications of these findings indicate the need for further emphasis on health education and lifestyle interventions at the community level to address prediabetes.